Rationales for Classroom Seating Arrangements: An EFL Teacher’s Voice - Sitti Nurfaidah; Abdul Halim; Hildayanti Hildayanti; Riski Riski (AL LUGHAWIYAAT, 2021)
This article aims to present a case study of an EFL teacher’s rationales in implementing certain seating arrangements in his classrooms. Using thematic analysis, the analyzed transcript of semi-structured interview indicates that the teacher’s rationales behind a certain seating arrangement in his class are various. The teacher reveals that traditional seating is considered suitable for explaining the lesson and also catching the students’ attention whenever they do not seem to be ready to study. Meanwhile, the U-shape seating is used when he wants to help and engage the students in activities which could foster their active participation. Pair seating becomes the teacher’s choice when he wants to encourage the shy students to speak. The teacher believes that group seating is of importance to help building the students’ confidence to speak. This study implies that the seating arrangement aspect in EFL classroom management should be well considered.Keywords:  EFL classroom; group seating; pair seating; seating arrangement; traditional seating; U-shape seating